The key issues of road design found from road safety inspections and road safety audits - Tumavičė, Aja; Vitkienė, Jūratė; Kaniušėnienė, Svaja; Kravcovas, Igoris; Lingytė, Ineta (International Conference “Environmental Engineering”, 2017)
In order to reduce accident rate on roads and streets more and more various road safety measures are being implemented each year. Nevertheless, road safety problem exists in most countries. For example, even though accident rate in Lithuania was almost halved (6372 to 3161 yearly accidents) from years 2004 to 2015, fatality rate is still quite high – 8.3 per 100000 people. New regulations, approved in 2008, dictate the need of carrying out road safety audits and road safety inspections for all road and street design projects. This paper presents most common road design errors and methods of fixing those errors based on Vilnius Gediminas Technical University Road Research Institute road safety auditors’ experience from years 2011 to 2016. Most common safety problems are organized and presented in groups ordered by their importance. Recommendations on how to improve road safety audit and inspection procedures in the future are formulated, as well as suggestions on improving road project design stage by taking most common flaw priority into consideration.